2018
DOI: 10.1002/hast.955
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Brain Death as a Legal Fiction: Is the Terminology the Problem?

Abstract: Brain death, or the determination of death by neurological criteria, has been described as a legal fiction. Legal fictions are devices by which the law treats two analogous things (in this case, biological death and brain death) in the same way so that the law developed for one can also cover the other. Some scholars argue that brain death should be understood as a fiction for two reasons: the way brain death is determined does not actually satisfy legal criteria requiring the permanent cessation of all brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The critics suggest that since several integrated biologic functions are maintained in patients who are determined BD/DNC, this determination is akin to a legal category, status, or fiction. Legal fictions are devices by which the law treats 2 analogous things (in this case, biological death and BD/DNC) in the same way so that the law developed for one can also apply to the other 14 . Legal fictions can be transparent, as for example when corporations are considered persons under the law.…”
Section: Is Brain Death Real (Biologic) Death?mentioning
confidence: 99%
See 1 more Smart Citation
“…The critics suggest that since several integrated biologic functions are maintained in patients who are determined BD/DNC, this determination is akin to a legal category, status, or fiction. Legal fictions are devices by which the law treats 2 analogous things (in this case, biological death and BD/DNC) in the same way so that the law developed for one can also apply to the other 14 . Legal fictions can be transparent, as for example when corporations are considered persons under the law.…”
Section: Is Brain Death Real (Biologic) Death?mentioning
confidence: 99%
“…Legal fictions are devices by which the law treats 2 analogous things (in this case, biological death and BD/DNC) in the same way so that the law developed for one can also apply to the other. [14] Legal fictions can be transparent, as for example when corporations are considered persons under the law. Critics argue that for a legal fiction to be ethically justifiable, the fact that BD is a legal fiction not aligned with the standard biological conception of death must be publicly acknowledged and made transparent.…”
Section: Introductionmentioning
confidence: 99%
“…39,[46][47][48][49][50][51][52] The basis of BD definitions continues to be questioned by some as being unscientific, or illogical, and contrived to facilitate organ donation. 2,39,42,[53][54][55] Others have suggested that BD determination criteria are not measuring loss that is truly irreversible. 54,64,65,68 More recently with the rise of DCDD, controversy over whether DCDD donors are really dead has become an increasing issue of debate.…”
Section: Controversies Around Brain Deathmentioning
confidence: 99%
“…Hot et al 53 Joffe 54 Miller and Truog 42 Shah 55 Shewmon 39 Truog et al 2 Belkin 56 Bernat et al 57 Shemie and Baker 35 Whether DCDD donors are really dead? Bernat 58 Bernat et al 57 Bernat 31 Shemie and Gardiner 27 Joffe 54 Shewmon 39 Truog 2…”
Section: Controversy Domain Key Proponents Key Opponentsmentioning
confidence: 99%
“…First, legal fictions are known to be fictions [ 27 , 28 ]. To treat BD as a legal fiction would require that the public is aware that the patient is not really biologically dead, but can be treated as such under the law [ 27 , 28 , 211 ]. At present, both the public and medical professionals are not informed that this is a legal fiction, and this would need to change.…”
Section: Potential Ways Forward (Table 5 )mentioning
confidence: 99%